Efektivitas Belajar Bahasa Mandarin di Tengah Pandemi - Rudiansyah, Rudiansyah (Pascasarjana, Universitas Negeri Gorontalo, 2021)
Mandarin is one of the most widely used international languages. However, who would have thought that this language is known as one of the most difficult languages to learn. Many people think so because, in Mandarin, there are more than 60,000 hanzi (characters or characters in Chinese) where each hanzi has a different way of writing or strokes and pronunciation. Speaking of pronunciation, in Mandarin there are 5 main tones used. However, in learning generally, only 4 tones are used. Despite these difficulties, many people still want to learn Mandarin. Especially during the current pandemic, many people are taking advantage of the opportunity to learn Mandarin online. This is what motivated the author to conduct research in order to find out about the impact on people who carry out learning Mandarin online. This study also aims to find out how effective online learning of Mandarin is, and what benefits people get when learning. The research method used is observation and survey, which shows that the effectiveness of learning Mandarin online is still considered very less effective. And the benefits that most people get is the use of the time that is quite efficient and the costs used are relatively more affordable.Keywords: Effectiveness; Learning; Mandarin; Pandemic